Cross-Functional Problems in the Customer Relationship Management Implementation of Relationship Marketing - Zainul Wasik; Sudarnice; Muchammad Saifuddin (PT. Mawadaku Sukses Solusindo, 2023)
The way businesses are structured has significantly changed as they transition from customer-based to product-based structures. The development of Customer Relationship Management, which is supported by the convergence of information systems and the creation of auxiliary software, is a major force behind this transition. It promises to dramatically enhance the application of relationship marketing principles. The three key issues that can help (or hurt) the growth of customer relationship management in the service industry are examined in this paper. These issues are organisational culture and communication, management metrics, and cross-functional integration, particularly between marketing and information technology.